Pengobatan Dukun Prewangan Ditinjau dari Akidah Islamiyah: Analisa Kepercayaan Masyarakat Desa Ngelokulon Kecamatan Mijen Kabupaten Demak - Rianissani, Khusniatul Farida (FIKRAH, 2018)
This article discusses the public trust in prewangan shaman treatment in Ngelokulon Village. Observations and interviews were conducted to obtain data. The phenomenology approach is used to analyze data. The results of this study indicate that the community still believes in prewangan dukun treatment even though it is prohibited in the teachings of their religion. Community trust in the treatment of prewangan herbalists is caused by several factors, namely the location of a shaman's house that is close to being in one village. Secondly, the information on the effectiveness of dukun treatment from others is spread. Third, relatively low wages. Fourth, the lack of public knowledge about treatment that is in accordance with Islamic law. Fifth, feel curious and want to try the prewangan shaman treatment for information and experiences of others. The importance of this article is to reveal that the practice of shamanism still exists amid modernity and changing times. This phenomenon is an ancestral heritage that still persists.